ALS701 : Research methodology / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2018)
This course is designed to give a practical and hands-on introduction to the use of qualitative and quantitative methods and conduct meaningful inquiry in applied language research. The course focuses on the essential elements of qualitative, quantitative research and mixed methods and types of research designs. Attention will be given to qualitative and quantitative research design and procedures for data collection, data processing and analysis. Because of the scope of the course is quite broad, it will not be possible to cover all of the details of all of the research methods that are currently being used. Nevertheless, at the end of the course, the students demonstrate their knowledge and skills required when conducting meaningful inquiry in applied language research.